Prevention of preterm birth among singleton pregnant women with an obtuse uterocervical angle: a quasi-experimental study on the value of cervical pessary combined with progesterone - Nguyen, Thi Hoang Trang; Vu, Van Tam; Nguyen, Vu Quoc Huy (Tạp chí Y Dược Huế, 2025)
Background: Micronized progesterone is an effective preterm birth prophylactic intervention in singleton pregnancies with short cervical length measured via transvaginal ultrasound in the second trimester. The use of cervical pessary as a preventive method for preterm birth has controversial findings when compared to progesterone-combining pessary, with the hypothesis that it narrows the uterocervical angle and reduces the risk of preterm birth. This study aimed to evaluate the value of cervical pessary combined with progesterone in the prevention of preterm birth among singleton pregnant women with a short cervix having uterocervical angles ≥ 95°. Methods: A quasi-experimental study with a nonequivalent-group design was conducted on 225 singleton pregnant women with a gestational age of 16+0 to 23+6 weeks, who had a cervical length of < 25 mm. Participants were assigned to two groups: prophylactic treatment with progesterone alone or progesterone combined with a cervical pessary. The association between cervical length, uterocervical angle (≥ 95° or ≥ 105°), and preterm birth outcomes (< 37 weeks or < 34 weeks) was assessed using a multivariable binary regression model. The difference was statistically significant (p < 0.05). Results: The probability of preterm birth (< 37 weeks) in the group of pregnant women with a uterocervical angle ≥ 95° treated with progesterone plus cervical pessary decreased compared to the progesterone-alone group, with an OR (95% CI) of 0.34 (0.15 - 0.8). In the group of pregnant women with a uterocervical angle ≥ 105°, the treatment by a cervical pessary plus progesterone yielded a lower rate of preterm birth < 37 weeks and < 34 weeks, with an OR (95% CI) of 0.03 (0.01 - 0.13) and 0.08 (0.02 - 0.35), respectively. Conclusions: The results of this study suggested that a cervical pessary has an added effect combined with progesterone in preventing preterm birth among singleton pregnant women with obtuse uterocervical angles. The preventive effect is stronger if the uterocervical angle measurement is ≥ 105°.